2020
DOI: 10.3389/fphar.2020.579241
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chinese Herbal Injections for the Treatment of Primary Nephrotic Syndrome: A Bayesian Network Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Considering the adverse reactions and side effects of immunosuppressive and cytotoxic drugs for the treatment of Primary Nephrotic Syndrome (PNS) and the extensive exploration of Chinese herbal injections (CHIs), systematic evaluation of the efficacy of different CHIs in the treatment of PNS is a key imperative. In this study, we performed a network meta-analysis to investigate the efficacy of CHIs in the treatment of PNS. Methods: A systematic literature review including studies published from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Enrichment analysis indicates that major pathways are advanced glycation end products, interleukin-17, tumor necrosis factor and Toll-like receptor signaling pathways (Shi et al, 2022). In addition, the combination of chemical drugs and Yinxingdamo injection or Danhong injection showed the best Chinese herbal injections compared with total clinical effectiveness, serum albumin and 24-h urinary protein excretion (Yu, H. et al, 2020). These findings demonstrate that traditional Chinese medicines can effectively ameliorate patients with IMN.…”
Section: Dna Methylation In Mnmentioning
confidence: 77%
“…Enrichment analysis indicates that major pathways are advanced glycation end products, interleukin-17, tumor necrosis factor and Toll-like receptor signaling pathways (Shi et al, 2022). In addition, the combination of chemical drugs and Yinxingdamo injection or Danhong injection showed the best Chinese herbal injections compared with total clinical effectiveness, serum albumin and 24-h urinary protein excretion (Yu, H. et al, 2020). These findings demonstrate that traditional Chinese medicines can effectively ameliorate patients with IMN.…”
Section: Dna Methylation In Mnmentioning
confidence: 77%
“…In addition, Yu et al (2020 ) reported that Chinese herbal injections were demonstrated to be superior to treatment of chemical drugs alone in the treatment of primary nephrotic syndrome and might be beneficial for patients with primary nephrotic syndrome. The combination of chemical drugs and Yinxingdamo injection and chemical drugs and Danhong injection had the potential to be the best Chinese herbal injections relative to total clinical effectiveness, serum albumin, and 24-h urinary protein excretion.…”
Section: Treatment Of Membranous Nephropathymentioning
confidence: 99%
“…As a branch of alternative medicine and ethnopharmacology that dates back to ancient China, traditional Chinese medicine (TCM) has been widely supported by clinical trials for its efficacy and lower rate of recurrence and undesirable side effects [13]. Developed based on traditional and modern medicine theories, TCM, or TCM-assisted treatments, with obvious advantages of high bioavailability and quick effect, is widely used for treating various clinical diseases and, to some extent, effective in relieving the clinical symptoms, such as primary nephrotic syndrome, poststroke depression, or communityacquired pneumonia [14][15][16]. Although several trials have examined the effectiveness of TCM in treating TS, there have been few studies to combine the available evidence of trials to explore the potential relationship between TCM and TS in terms of efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%